2009
DOI: 10.1128/iai.01280-08
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoethanolamine Substitution of Lipid A and Resistance ofNeisseria gonorrhoeaeto Cationic Antimicrobial Peptides and Complement-Mediated Killing by Normal Human Serum

Abstract: The capacity of Neisseria gonorrhoeae to cause disseminated gonococcal infection requires that such strains resist the bactericidal action of normal human serum. The bactericidal action of normal human serum against N. gonorrhoeae is mediated by the classical complement pathway through an antibody-dependent mechanism. The mechanism(s) by which certain strains of gonococci resist normal human serum is not fully understood, but alterations in lipooligosaccharide structure can affect such resistance. During an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
152
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(160 citation statements)
references
References 55 publications
(55 reference statements)
8
152
0
Order By: Relevance
“…In two separate experiments, we found (data not presented) that, on average, the lptA::spc mutant exhibited increased susceptibility to 16 g/ml of LL-37 (5% survival) compared to the susceptibilities of the wild-type and C=lptA mutant strains (25% and 35% survival, respectively); the scrambled peptide did not exhibit bactericidal action against any of the test strains. This finding is consistent with earlier results that showed that lptA null mutants are more susceptible than wild-type gonococci to PMB (14,17).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…In two separate experiments, we found (data not presented) that, on average, the lptA::spc mutant exhibited increased susceptibility to 16 g/ml of LL-37 (5% survival) compared to the susceptibilities of the wild-type and C=lptA mutant strains (25% and 35% survival, respectively); the scrambled peptide did not exhibit bactericidal action against any of the test strains. This finding is consistent with earlier results that showed that lptA null mutants are more susceptible than wild-type gonococci to PMB (14,17).…”
Section: Resultssupporting
confidence: 83%
“…The increased fitness of the C=lptA mutant relative to the wild-type strain may be due to higher expression of the lptA gene in the C=lptA mutant. In this strain, the complementing lptA gene is under the control of the lac promoter (14), and increased expression of isopropyl-␤-Dthiogalactopyranoside (IPTG)-inducible genes has been demonstrated previously during murine infection (17,31). These results suggest that the PEA moiety on wild-type lipid A is beneficial to N. gonorrhoeae during infection and provides a fitness advantage over the fitness of gonococci devoid of PEA-decorated lipid A.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Modification of lipid A with PEA has been found to increase the resistance of N. gonorrhoeae to complement killing in normal human serum by increasing the binding of the complement regulatory protein C4b-binding protein and increasing resistance to endogenous cationic antimicrobial peptides (41,42). In N. meningitidis, modification of lipid A with PEA has been shown to inhibit bactericidal activity of cathepsin G within neutrophil extracellular traps (4) and to increase the adhesion of the bacteria to human cells (5).…”
Section: Table 4 Expression Of Pea (A) O-acetate (B) and Sialic Acimentioning
confidence: 99%